Understanding environmental problems in Dinaric karst - Nicod, Jean (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
The main regions of the Dinaric karst, the Kras, the islands and low plateaus of the Dalmatian coast, present the types of land use typical of Mediterranean countries and which produce changes in the surface, e.g., deforestation and the adaptation of the karst surface for agriculture, the use of extracted stones and land reclamation. The evolution of the landscape and systems of adapting agriculture to karstic terrains in Kras and Dalmatian countries make it possible to establish comparisons with other karstic countries, i.e., Provence, the Causses and Puglia, conversely, this research provides better knowledge of the aspects and workings of Dinaric karsts, particularly the evolution of landscape, the growth of karren-fields and the geomorphological and hydrological changes in the poljes.
Keywords: agriculture; Dinarski kras; ecology; ekologija; ekološko ravnotežje; geomorfologija; geomorphology; kmetijstvo; kras (geologija); raba tal